Genetic factors influencing the development and treatment of cognitive impairment and psychosis in Parkinson’s disease - Pérez Lloret, Santiago (2019)
Fil: Pérez Lloret, Santiago. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina